Two new species of Zwicknia Murányi, with molecular data on the phylogenetic position of the genus (Plecoptera, Capniidae) - Boumans, Louis; Murányi, Dávid (Zootaxa, 2014)
Analyses of the nuclear DNA marker 28S confirm the distinctness of the recently erected stonefly genus Zwicknia Murányi 2014, which encompasses the species until recently referred to as ‘Capnia bifrons.’ Two new species are described and illustrated with line drawings: Z. westermanni Boumans & Murányi, sp. n. from Germany and France, and Z. komica Murányi & Boumans, sp. n. from the Komi Republic in northwestern Russia. The intersexual communication of the former species is described in detail. A phylogenetic analysis of 87 sequences of the mitochondrial marker cytochrome c oxidase I (COI) representing the six described European species of Zwicknia and outgroup taxa reveals large genetic distances within the species Z. rupprechti and Z. bifrons, while the haploclade including all specimens of the latter species also includes Z. acuta and Z. westermanni. The mitochondrial phylogeny is assumed not to represent the species phylogeny. In contrast, a phylogeny of the nuclear markers 28S and ITS reveals that Z. rupprechti and Z. westermanni are more closely related to each other than either is to Z. bifrons. This finding is in line with the drumming patterns of the former two species being relatively similar.